Specification for copper and copper-alloy bare welding rods and electrodes (American Welding Society ; Reproduced by World Engineering Xchange (WEX) with the permission of AWS under royalty agreement, 2007)
"This specification prescribes the requirements for classifications of copper and copper-alloy electrodes and rods for gas shielded metal arc, gas shielded tungsten arc, and plasma arc welding. Classification is based on chemical composition of the filler metal. Additional requirements are included for manufacture, sizes, lengths and packaging. A guide is appended to the specification as a source of information concerning the classification system employed and intended use of the electrodes. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other."